Lovely knits for little girls : 20 just-right patterns, just for girls - Sondergaard, Vibe. (Newtown, CT : Taunton Press, 2012)
"Knit patterns for little girls"--
Sweaters -- Cardigans -- Dresses and tops -- Skirts and wraps -- Charming accessories.
Keywords: Knitting -- Patterns; Knitwear; Girls' clothing